The role of gut microbiota in health and diseases - Deasy Fetarayani; Handoko Hariyono; Gatot Soegiarto (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2021)
ABSTRACTABSTRACTMicrobiota contributes a crucial part in the human hosts' health and actively provides to the emergence of various diseases. The optimal composition of healthy intestinal microbiota varies from person to person. The more various and abundant of the microbiota, the greater their resistance to outside hazards. Colonization of the microbiota in the human body starts after delivery and develops continuously from infant to adult. The largest microbial colony is constructed in the lower part of the adult human digestive tract. The composition of the human intestinal microbiota alters promptly during the beginning of life and is steady. It has been described the close relationship among dysbiosis of the intestinal microbiota with intestinal and non-intestinal diseases. Nevertheless, it is uncertain whether dysbiosis is the culprit of the disease or only as a result of the disease. Human microbiota's role must be investigated more deeply so that later it can be developed for the prevention, diagnosis of disease, and more effective treatment strategies in the future. In this minireview, we will describe the development of the gut microbiota, its interaction with our bodily systems and defense, the multiple causes of dysbiosis, and its impact on several metabolic in inflammatory diseases in humans. With this insight, it is hoped that we can be more cautious about using antibiotics, avoid things that lead to dysbiosis, and handle diseases more holistically, putting the balance of the microbiota into account. Keywords:  human, microbiota, gastrointestinal tract, dysbiosis, health and diseaseCorresponding author: deasyfetarayani@gmail.com